2023
DOI: 10.3390/genes14040861
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study on Reproductive Traits Using Imputation-Based Whole-Genome Sequence Data in Yorkshire Pigs

Abstract: Reproductive traits have a key impact on production efficiency in the pig industry. It is necessary to identify the genetic structure of potential genes that influence reproductive traits. In this study, a genome-wide association study (GWAS) based on chip and imputed data of five reproductive traits, namely, total number born (TNB), number born alive (NBA), litter birth weight (LBW), gestation length (GL), and number of weaned (NW), was performed in Yorkshire pigs. In total, 272 of 2844 pigs with reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Given the large number of existing genome-wide association studies in pigs 6 , we expect this resource to be highly utilized and impactful. Indeed, more than 130,000 genomes were imputed in the first year since the server became public, including a recent study that found SWIM imputed genomes to detect more significant SNPs compared to other platforms 28 . All existing studies using SNP arrays can be improved by a simple imputation followed by GWAS without additional data.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large number of existing genome-wide association studies in pigs 6 , we expect this resource to be highly utilized and impactful. Indeed, more than 130,000 genomes were imputed in the first year since the server became public, including a recent study that found SWIM imputed genomes to detect more significant SNPs compared to other platforms 28 . All existing studies using SNP arrays can be improved by a simple imputation followed by GWAS without additional data.…”
Section: Discussionmentioning
confidence: 99%
“…However, testing multiple markers simultaneously is more advantageous, and this can be done by fitting pseudo QTNs in addition to the testing markers in a stepwise MLM, which is called multi-locus mixed model [60]. Liu et al developed an improved method by using fixedeffect model and random-effect models iteratively, namely the FarmCPU, which has strong advantages for eliminating confounding effects, improving statistical power, and reducing computing time [49], and this approach has been applied to investigate the genetic markers for meat quality, reproduction, and growth traits in pigs [61][62][63]. Kaler et al have compared the different statistical models used for GWAS, which indicated that the FarmCPU performed better than other models based on the Q-Q plot and the identification of the known QTLs in a simulation dataset [64].…”
Section: Software and Algorithmsmentioning
confidence: 99%